Current characteristics of dialysis therapy in Korea: 2015 registry data focusing on elderly patients - Dong-Chan Jin; Sung-Ro Yun; Seoung Woo Lee; Sang-Woong Han; Won Kim; Jongha Park (The Korean Society of Nephrology, 2016)
Because of increases in the elderly population and diabetic patients, the proportion of elderly among dialysis patients has rapidly increased during the last decades. The mortality and morbidity of these elderly dialysis patients are obviously much higher than those of young patients, but large analytic studies about elderly dialysis patients' characteristics have rarely been published. The registry committee of the Korean Society of Nephrology has collected data about dialysis therapy in Korea through an Internet online registry program and analyzed the characteristics. A survey on elderly dialysis patients showed that more than 50% of elderly (65 years and older) patients had diabetic nephropathy as the cause of end-stage renal disease, and approximately 21% of elderly dialysis patients had hypertensive nephrosclerosis. The proportion of elderly hemodialysis (HD) patients with native vessel arteriovenous fistula as vascular access for HD was lower than that of young (under 65 years) HD patients (69% vs. 80%). Although the vascular access was poor and small surface area dialyzers were used for the elderly HD patients, the dialysis adequacy data of elderly patients were better than those of young patients. The laboratory data of elderly dialysis patients were not very different from those of young patients, but poor nutrition factors were observed in the elderly dialysis patients. Although small surface area dialyzers were used for elderly HD patients, the urea reduction ratio and Kt/V were higher in elderly HD patients than in young patients.